2018
DOI: 10.1111/maps.13038
|View full text |Cite
|
Sign up to set email alerts
|

Shapes of chondrules determined from the petrofabric of the CR2 chondrite NWA 801

Abstract: The approximately spherical shapes of chondrules has long been attributed to surface tension acting on ~1 mm melt droplets that formed and cooled in the microgravity field of the solar nebula. However, chondrule shapes commonly depart significantly from spherical. In this study, 109 chondrules in a sample of CR2 chondrite NWA 801 were imaged by X‐ray computed tomography and best‐fitted to ellipsoids. The analysis confirms that many chondrules are indeed not spherical, and also that the chondrules’ collective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…tion of chondrules seems to have a greater diversity of shape than those of the NWA 801 CR chondrite investigated byCharles et al (2018).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…tion of chondrules seems to have a greater diversity of shape than those of the NWA 801 CR chondrite investigated byCharles et al (2018).…”
mentioning
confidence: 77%
“…It is commonly thought that chondrules are nominally spherical in shape, although deeper inspection indicates nonspherical, ellipsoidal shapes due to both pre-accretionary (Tsuchiyama et al, 2003;Weisberg & Prinz, 1996) and post-accretionary or parent body processes acting on the chondrules (Cain et al, 1986;Charles, Robin, Davis, and McCausland (2018)). To quantify the shapes of chondrules and to investigate if chondrules within our datasets define a petrofabric within a chondrite, we used a procedure like that found in Friedrich et al (2008).…”
Section: Digital Methods For Chondrule Segmentation and Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, 2D measurements underestimate the departure from sphericity of chondrules. After correcting for postaccretional deformation, Charles et al (2018) still found that 100 out of 109 chondrules of CR2 chondrite NWA 801 examined in X-ray tomography had aspect ratios above 1.1, and 52 above 1.3. Twelve of the 20 Allende (CV3) chondrules studied by Tsuchiyama et al (2003) with the same technique had aspect ratios exceeding 1.1.…”
Section: Implications On Compound Chondrule Statisticsmentioning
confidence: 98%
“…They should further characterize the possibility of postaccretional deformation, e.g. shear or lineation (Charles et al 2018). The CO chondrites may e.g.…”
Section: La-icp-ms Spots Straddle the Putative Boundary And Show Indi...mentioning
confidence: 99%